Evaluating the acceptance of teleaudiology for tinnitus management among audiologists and patients with tinnitus in Malaysia - Nizamuddin, Shameera (2024)
Teleaudiology for tinnitus management has not been studied in Malaysia emphasizing the need for preliminary insights from users, particularly audiologists and patients with tinnitus. This study aimed to assess the acceptance of teleaudiology for tinnitus management among audiologists and patients with tinnitus in Malaysia. The study was conducted in two phases. In phase I, four expert panels translated and adapted the Telehealth Usability Questionnaire (TUQ) into the Bahasa Melayu version for tinnitus management. A cognitive debriefing involving a small group of audiologists and patients with tinnitus was conducted to ensure the comprehensibility of the Bahasa Melayu version. Content validity was evaluated using content validity indexes (Item-CVI and Scale-CVI) and kappa values by nine experts. All items were satisfactory (I-CVI ≥ .78, S-CVI ≥ .96 and kappa analysis ≥ .78). Internal consistency was assessed using Cronbach's alpha (a) and item-to-total correlation on 10 audiologists and 10 patients with tinnitus. The initialMyTUQ-T demonstrated good Cronbach’s alphas of .758 to .893 for audiologists and .740 to .850 for patients with tinnitus. The item-to-total correlation was very good ranging from .550 to .945 for audiologists and .578 to .948 for patients with tinnitus. In phase II, a cross-sectional study utilized the validated and reliable MyTUQ-T to assess the acceptance of teleaudiology for tinnitus management among 42 audiologists, mean age 36.71 (± 4.74), and 84 patients with tinnitus, mean age 46.04 (± 14.52) across Malaysia. Audiologists and patients with tinnitus are somewhat agree to accept the use of teleaudiology for tinnitus management in Malaysia. Usefulness subscale received the highest average score, while the reliability subscale obtained the lowest average score in both categories of respondents. Spearman's correlation analysis was used to examine the correlation between the five usability factors in the MyTUQ-T. A strong positive correlation was identified between all usability factors for both audiologists and patients with tinnitus. The highest correlation is between the reliability factor and the effectiveness factor in both groups of respondents, with a correlation coefficient (r) .888 for audiologists (p = .000, r = .888) and .923 for patients with tinnitus (p =. 000, r = .923). Multiple linear regressions (MLR) were applied to explore the associations between sociodemographic characteristics, hearing loss laterality, tinnitus severity and acceptance of teleaudiology for tinnitus management. Gender significantly influenced audiologists’ acceptance (β = 0.800; 95% CI 0.06, 1.54; p = .035) and age significantly influenced patients’ acceptance (β = - 0.019; 95% CI - 0.04, 0.00; p = .027). However, no significant relationships were found between acceptance and other factors (p ≥ .05). In conclusion, both audiologists and patients with tinnitus in Malaysia are approaching the level of acceptance to accept the use of teleaudiology for tinnitus management. Further research is needed to understand how gender among audiologists and age among patients with tinnitus influence their acceptance of teleaudiology for tinnitus management. This understanding will aid in developing effective management plans for tinnitus care in the future